The Mediating Role of Customer Satisfaction on the Effect of Product Quality and Brand Equity on Customer Loyalty at Uniqlo Indonesia - Valentina, Dinda Putri; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how customer happiness influences the relationship between product quality, brand equity, and customer loyalty at Uniqlo Indonesia. One hundred customers made up the sample. The SmartPLS 4.0 program's outer model, inner model, and hypothesis testing were all used in this study's test results. These studies' findings demonstrate that: (1) customer satisfaction has no discernible impact on loyalty; (2) brand equity has a positive and significant effect on loyalty; (3) product quality has no discernible impact on satisfaction; (4) brand equity has a positive and significant effect on satisfaction; (5) customer satisfaction has a positive and significant effect on loyalty; and (6) customer satisfaction does not mediate the effect of product quality on the loyalty of Uniqlo Indonesia customers, (7) In Indonesia, the relationship between brand equity and Uniqlo client loyalty is substantially mediated by customer satisfaction.